Developing an objective assessment of surgical performance from operating room video and surgical imagery. Issue 2 (3rd April 2018) - Taylor, Leah K.; Thomas, Geb W.; Karam, Matthew D.; Kreiter, Clarence D.; Anderson, Donald D.
ABSTRACT: An unbiased, repeatable process for assessing operating room performance is an important step toward quantifying the relationship between surgical training and performance. Hip fracture surgeries offer a promising first target in orthopedic trauma because they are common and they offer quantitative performance metrics that can be assessed from video recordings and intraoperative fluoroscopic images. Hip fracture repair surgeries were recorded using a head-mounted point-of-view camera. Intraoperative fluoroscopic images were also saved. The following performance metrics were analyzed: duration of wire navigation, number of fluoroscopic images collected, degree of intervention by the surgeon's supervisor, and the tip-apex distance (TAD). Two orthopedic traumatologists graded surgical performance in each video independently using an Skills (OSATS). Wire navigation duration correlated with weeks into residency and prior cases logged. TAD correlated with cases logged. There was no significant correlation between the OSATS total score and experience metrics. Total OSATS score correlated with duration and number of fluoroscopic images. Our results indicate that two metrics of hip fracture wire navigation performance—duration and TAD—significantly differentiate surgical experience. The methods presented have the potential to provide truly objective assessment of resident technical performance in the OR.